The Influence of Intellectual Capital on Innovation and Creating Competitive Advantage: The Mediating Role of Knowledge Sharing and Innovation - Alfatis, Safia; Nassani, Abdelmohsen (The Arab Journal of Administration, 2023)
This paper aims to evaluate the influence of intellectual capital on innovation and creating competitive advantage with mediating role of knowledge sharing and innovation in Saudi companies. Data was collected from employees of the Saudi private sector using an online questionnaire, path analysis was demonstrated using SPSS, and the best fit of the model was tested through AMOS. The findings highlighted a positive relationship among the variables in this study. Human capital and structural capital in Saudi companies have a positive impact on knowledge sharing. Similarly, knowledge sharing positively influenced innovation as well as mediated the effect between intellectual capital and innovation. Results also indicated a mediating effect of innovation between knowledge sharing and competitive advantage, and findings were highly consistent with the predicted hypotheses. Finally, future researchers are recommended to investigate the impact of the other intellectual capital dimensions such as relational and psychological capita on innovation and competitive features in Saudi organizations.